Koncepcja J. Rawlsa racjonalnej sprawiedliwości jako bezstronności a zagadnienia etyki życia gospodarczego - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2008)
Rawls’s theory of justice is based on Kant’s ethics and the theory of social contract. Rawls tries to obey two rules: of universalizations and universality and of the maximization for the least privileged. His theory can be used to judge the ethical position of business firms. It follows from my studies that a just organization of a firm is rare in times of transformation. This may be another reason for mass emigration and it must be taken into account in future debates of the economic development.